Organs for Transplantation: The Singapore Experience - Teo, Bernard (The Hastings Center report, 1991)
Singapore's Human Organ Transplant Act presumes that competent adults consent to donate their kidneys in the event of a fatal accident, unless they have refused in writing. No family consent is required. What can other countries wishing to implement a presumed-consent model of organ donation learn from Singapore's experience?